The procedural efficiency, efficacy and safety of high power and short duration ablation in patients with atrial fibrillation: A systemic review and meta-analysis. (15th February 2021) - Sun, Xuerong; Qi, Peng; Yang, Bin; Li, Zhonghe; Bie, Zidong; Li, Xuexun
Highlights: This is the first systemic review and meta-analysis on the high power short time ablation for atrial fibrillation patients. Compared with conventional ablation therapy, high power short time ablation could achieve better efficacy outcomes. As for the procedural efficiency, shorter ablation time, procedure time and fluoroscopy time were spent in the new approach. High power short time ablation was reported as safe as conventional ablation therapy.